Predicting satisfaction with democracy in Germany using local economic conditions, social capital, and individual characteristics - Tim Friehe; Christian Pfeifer (Economics of Governance, 2024)
This paper explores the empirical relationship between local economic conditions, social capital, and individual characteristics on the one hand and satisfaction with democracy on the other hand, using detailed information from the German Socio-Economic Panel. In contrast to previous literature, we focus on economic conditions at the state level instead of the national one. We find that local economic conditions, proxies of social capital, and individual characteristics (e.g., risk attitude, reciprocity, past unemployment experience) are important correlates of satisfaction with democracy and that some heterogeneity between genders, West and East Germany, and people with and without college degree exists in the data.
Keywords: H11; P16; 330; Democracy; Satisfaction; Economic conditions; SOEP